Journal of a Residence in Ashantee - Dupuis, J. (Henry Colburn, London., 1824)
The British trade with the Gold Coast of Africa was placed by charter, in the reign of Charles II, under the control of the Royal African Company, whose governor – general (the Governor of Cape Coast Castle) and council (consisting principally of the commandants of the subordinates forts) had direction of matters on the African shore, acting, of late years, under instructions sent from England by a body of men chosen for that employ, called the African Committee.
Keywords: Residence; Royal African Company; Trade; Ashanti; Gold Coast